Reversing the Approach to Null Subjects: A Perspective from Language Acquisition - Duguine, Maia (Frontiers in Psychology, 2017)
This paper proposes a new model for null subjects, and focuses on its implications for language development. The literature on pro-drop generally considers that not allowing null subjects is the default option in natural languages, and appeals to particular morphosyntactic mechanisms in order to account for those languages in which the subject can be omitted. Shifting the perspective, the inverse approach postulates that pro-drop is (almost) a default grammatical setting, and that non-pro-drop results from the intervention of independent factors that block pro-drop in the derivation. The paper explores the consequences of the inverse approach in the domain of language acquisition, arguing that this model allows to account for a number of properties of child languages. It opens an avenue of research worth exploring, one that could give new solutions to old problems.